Assessing adherence to objective disease monitoring and outcomes with adalimumab in a real-world IBD cohort. Issue 8 (August 2021) - Al Khoury, A.; Xiao, Y.; Golovics, P.A.; Kohen, R.; Afif, W.; Wild, G.; Friedman, G.; Galiatsatos, P.; Hilzenrat, N.; Szilagyi, A.; Wyse, J.; Cohen, A.; et al.
Abstract: Background: Data suggests that tight objective monitoring may improve clinical outcomes in IBD. Aim: To assess the adherence to serial tight objective monitoring(clinical and biomarkers) and its effect on clinical outcomes. Methods: We retrospectively reviewed the chart of 428 consecutive IBD patients started on adalimumab between January 1, 2015–January 1, 2019 [338 Crohn's disease(CD), 90 ulcerative colitis(UC)]. Clinical symptoms(assessed by Harvey-Bradshaw-Index, partial Mayo), C-Reactive Protein(CRP), and fecal calprotectin(FCAL) assessments were captured at treatment initiation and at 3, 6, 9, and12 months. Dose optimization and drug sustainability curves were plotted by Kaplan-Meier method. Results: Clinical evaluation was available in nearly all patients at 3(CD-UC:95–94%), 6(90–83%), 9(86–85%) and 12(96–89%) months. CRP testing frequency decreased in CD patients over time. Compliance to serial FCAL testing was low. Clinical remission at one-year was higher in patients adherent to early assessment visit at 3 months( p = 0.001 for CD and UC). Adherence to early follow-up resulted in earlier dose optimization in CD and UC patients(pLogrank=0.026 for UC & p = 0.09 for CD). Overall drug sustainability did not differ. Conclusion: Clinical & CRP, but not FCAL, were frequently assessed in patients starting adalimumab. Adherence to early objective combined follow-up visits resulted in earlier dose optimization, improved one-year clinical outcomes but did not change drug sustainability.